Dengue Virus Type 2: Protein Binding and Active Replication in Human Central Nervous System Cells. (4th November 2013) - Salazar, Ma Isabel; Pérez-García, Marissa; Terreros-Tinoco, Marisol; Castro-Mussot, María Eugenia; Diegopérez-Ramírez, Jaime; Ramírez-Reyes, Alma Griselda; Aguilera, Penélope; Cedillo-Barrón, Leticia; García-Flores, María Martha
Abstract : An increased number of dengue cases with neurological complications have been reported in recent years. The lack of reliable animal models for dengue has hindered studies on dengue virus (DENV) pathogenesis and cellular tropism in vivo . We further investigate the tropism of DENV for the human central nervous system (CNS), characterizing DENV interactions with cell surface proteins in human CNS cells by virus overlay protein binding assays (VOPBA) and coimmunoprecipitations. In VOPBA, three membrane proteins (60, 70, and 130 kDa) from the gray matter bound the entire virus particle, whereas only a 70 kDa protein bound in white matter. The coimmunoprecipitation assays revealed three proteins from gray matter consistently binding virus particles, one clearly distinguishable protein ( ~ 32 kDa) and two less apparent proteins (100 and 130 kDa). Monoclonal anti-NS3 targeted the virus protein in primary cell cultures of human CNS treated with DENV-2, which also stained positive for NeuH, a neuron-specific marker. Thus, our results indicate (1) that DENV-2 exhibited a direct tropism for human neurons and (2) that human neurons sustain an active DENV replication as was demonstrated by the presence of the NS3 viral antigen in primary cultures of these cells treated with DENV-2.